Modulation of Respiratory System by Limb Muscle Afferents in Intact and Injured Spinal Cord - Shevtsova, Natalia A.; Marchenko, Vitaliy; Bezdudnaya, Tatiana (Frontiers in Neuroscience, 2019)
Breathing constantly adapts to environmental, metabolic or behavioral changes by responding to different sensory information, including afferent feedback from muscles. Importantly, not just respiratory muscle feedback influences breathing. Afferent sensory information from rhythmically moving limbs has also been shown to play an essential role in the breathing. The present review will discuss the neuronal mechanisms of respiratory modulation by activation of peripheral muscles that usually occurs during locomotion or exercise. An understanding of these mechanisms and finding the most effective approaches to regulate respiratory motor output by stimulation of limb muscles could be extremely beneficial for people with respiratory dysfunctions. Specific attention in the present review is given to the muscle stimulation to treat respiratory deficits following cervical spinal cord injury.